2009
DOI: 10.1002/cjoc.200990114
|View full text |Cite
|
Sign up to set email alerts
|

π Type Lithium Bond Interaction between Ethylene, Acetylene, or Benzene and Amido‐lithium

Abstract: The optimization geometries and interaction energy corrected by basis set super-position error (BSSE) of the lithium bond complexes between ethylene, acetylene, or benzene and amido-lithium have been calculated at the B3LYP/6-311++G** and MP2/6-311++G** levels. And only one configuration was obtained for each lithium bond system. All the equilibrium geometries were confirmed to be stable state by analytical frequency computations. The calculations showed that all the N(2)-Li(4) bond lengths increased obviously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 30 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Recently, much attention has been paid to hydrogen bond-like interactions, such as lithium bonding and halogen bonding. The existence of lithium bonding was first suggested as a possibility by Shigorin in 1959 due to the fact that lithium is a congener of hydrogen, but the study for it is not very much. Even so, it has been demonstrated that, like hydrogen bonding, it can also be formed between the Li atom and different bases. Lithium–hydride interaction was predicted and characterized in HMgH–LiX (X = H, OH, F, CCH, CN, and NC) complexes .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much attention has been paid to hydrogen bond-like interactions, such as lithium bonding and halogen bonding. The existence of lithium bonding was first suggested as a possibility by Shigorin in 1959 due to the fact that lithium is a congener of hydrogen, but the study for it is not very much. Even so, it has been demonstrated that, like hydrogen bonding, it can also be formed between the Li atom and different bases. Lithium–hydride interaction was predicted and characterized in HMgH–LiX (X = H, OH, F, CCH, CN, and NC) complexes .…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the electronic similarity among lithium, sodium, and hydrogen elements, efforts have also been devoted to exploring the possibility that lithium or sodium salt molecules serve as Lewis acids to interact with electron donors. Consequently, the existence of lithium bonding [29][30][31] and sodium bonding 32,33 interactions has been put forward. In 2009, Yáñez and co-workers further enriched the study of non-covalent interactions with a series of beryllium bonding systems in which the BeX 2 (X ¼ H, F, Cl, OH) molecules take the role of electron acceptor.…”
Section: Introductionmentioning
confidence: 99%